Práticas pedagógicas e acessibilidade curricular nos anos finais do ensino fundamental - Lavarda, Eliane Sperandei (2023)
This research was conducted in the Special Education, Inclusion, and Difference Research Line of the Postgraduate Program in Education at the Federal University of Santa Maria - PPGE/UFSM, and within the scope of the Studies and Research Center on Schooling and Inclusion - NUEPEI. The research question focused on which elements constitute the construction of pedagogical practices that promote curricular accessibility for students in special education in the final years of elementary education. To address this question, the research aimed to: understand, analyze, and redefine the pedagogical practices of teachers in the final years of elementary education regarding curricular accessibility for students in special education. Specific objectives derived from the research were: to understand and analyze the construction of pedagogical practices carried out by teachers in the final years of elementary education; to engage in reflection with teachers on how democratic pedagogical practices are formed, enabling access to school knowledge; to propose the construction and development of practical experiences from the perspective of differentiated pedagogy and universal learning design; and to redefine the construction of pedagogical practices for teachers in the final years of elementary education. Aligned with systemic thinking, the theoretical and methodological framework used was based on the contributions of Vasconcellos (2002), Maturana (1990, 1993, 1998, 2014), Maturana and Varela (2001), Maturana and Rezepka (2000), Bateson (1986), and Pellanda (2009). Regarding pedagogical thought, the scenario was drawn from Meirieu's Differentiated Pedagogy (1998, 2002, 2005, 2006) and Universal Design for Learning, CAST (2018), and Heredero (2020). The curriculum was approached from the perspectives of Sacristán (2013, 2017), Goodson (2008), and Macedo et al (2004). Following a qualitative research approach and aligned with systemic thinking, the Bricolage method was used, considering research as a complex experience that explores the relationships connecting the research object to the context in which it exists, with the observer as an integral part of the process. Data collection took place in the Municipal Education Network of Santa Maria, in a school that caters to both early childhood education and the final years of elementary education. The research subjects included teachers from all disciplines in the final years of elementary education, the pedagogical coordinator, and the special education teacher. Narrative interviews were conducted at the beginning and end of the investigative process, with nine participants in the initial interview and seven in the final interviews. Four reflective meetings took place, constituting formative moments with the participation of seven teachers. The practical experience of designing and implementing a lesson plan based on the principles of Universal Design for Learning (UDL) involved two teachers. The production of data through various instruments resulted in relevant and powerful information for building connections between the observed realities. Three analytical axes were constructed: "The constitution of pedagogical practices and the school curriculum," "Movements in pedagogical practice based on the principles of UDL and Differentiated Pedagogy," and "Redefining pedagogical practices." At the end of the investigation, the possibility of redefining the pedagogical practices of teachers in the final years of elementary education is emphasized, aiming for them to be democratic and accessible when based on Differentiated Pedagogy and Universal Design for Learning.